Peran Kepemimpinan sebagai Pendorong Utama Transformasi Organisasi - Khairunnisa, Aisyah; Khodijah, Nyayu; Febriyanti, Febriyanti (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – The study aims to investigate how leadership influences and facilitates organizational change, with a focus on the education sector. Through literature analysis, this article highlights the importance of adaptability and flexibility in leadership to align with the evolving needs of change in the digital and globalization era.Method – Using a literature review approach, this research examines the role of leadership in organizational change, particularly within the educational context, emphasizing adaptability and flexibility as essential traits.Findings – The findings underscore the significant impact of effective leadership on the success and sustainability of the change process at various organizational levels. Effective leadership plays a crucial role in navigating organizational change, particularly in dynamic environments marked by digitalization and globalization. Research Implications – This research provides an understanding of the importance of leadership in driving organizational change, offering practical insights for leaders to enhance organizational performance and adaptation amid evolving challenges in the modern era. However, the study also acknowledges limitations, such as the need for further empirical research to validate the findings and the potential contextual differences in the applicability of leadership approaches across diverse organizational settings.